Mengukur kualitas pendidikan di Indonesia - Wahyudi, Lestari Eko; Mulyana, Alfiyan; Dhiaz, Ajrin; Ghandari, Dewi; Putra Dinata, Zidan; Fitoriq, Muallimu; Hasyim, M. Nur (Lembaga Pendidikan Ma'arif Nahdlatul Ulama, Kabupaten Malang, Indonesia, 2022)
Education is one of the efforts to improve the quality of human resources. This method uses a literature study with document-based and internet-based research as a reference for data that will be discussed and studied according to research questions and aims to determine the quality of education in Indonesia. The quality of education is said to be good if it has good input and output values, meaning that these values ​​can later solve problems in society. The quality of education in Indonesia is still very low compared to other countries in the Southeast Asian region. However, the government is always trying to improve the quality of education for the community in order to create superior human resources so that they can compete with outsiders.